PM2.5 Exposure Risk Analysis Around Mining Area Wolo District - Rahman Rauf; Yunita Amraeni; Leniarti Ali (Universitas Mandala Waluya, 2021)
Particulate measuring below 2.5 microns have a very large effect on the body and the atmospheric environment, and are harmful to the respiratory organs and can cause asthma and lung disorders. The objective of this study was to identify the risk of PM2.5 exposure to communities in residential areas around nickel mining in Wolo District, Kolaka Regency. This study uses a descriptive observational method with a total sample of 324 respondents. The results showed that the highest value of the PM2.5 concentration measurement was 68.8 g/Nm3. The measurement of PM2.5 concentration has normally distributed so that the mean value is used as the PM2.5 concentration value. The risk of health living in the vicinity of the PT. Ceria Nugraha Indotama due to PM2.5 exposure of 0.093 mg/kg/day for 5 years (RQ<1) and 3.59 mg/kg/day for 30 years (RQ>1). It is necessary to plant green trees around the mining area to reduce the concentration of particulates in the air and to control the distance of the population to at least 2 km from the industrial center.